Design and synthesis of new 1,2,4-oxadiazole/quinazoline-4-one hybrids with antiproliferative activity as multitargeted inhibitors - Mohamed, Amira M.; Abou-Ghadir, Ola M. F.; Mostafa, Yaser A.; Dahlous, Kholood A.; Bräse, Stefan; Youssif, Bahaa G. M. (Frontiers in Chemistry, 2024)
Introduction The combination of BRAF and tyrosine kinase (TK) inhibitors has been demonstrated to be highly effective in inhibiting tumor development and is an approach for overcoming resistance in clinical trials. Accordingly, a novel series of 1,2,4-oxadiazole/quinazoline-4-one hybrids was developed as antiproliferative multitargeted inhibitors. Methods The structures of the newly synthesized compounds 9a-o were validated using IR, NMR, MS, and elemental techniques. 9a–o were tested as antiproliferative agents. Results and Discussion The results showed that the majority of the tested compounds showed significant antiproliferative action with 9b, 9c, 9h, 9k, and 9l being the most potent. Compounds 9b, 9c, 9h, 9k, and 9l were tested as EGFR and BRAFV600E inhibitors. These in vitro tests revealed that compounds 9b, 9c, and 9h are strong antiproliferative agents that may act as dual EGFR/BRAFV600E inhibitors. 9b, 9c, and 9h were further investigated for their inhibitory effect on mutant EGFR (EGFRT790M), and the results showed that the tested compounds had considerable inhibitory action. Cell cycle study and apoptosis detection demonstrated that compound 9b exhibits cell cycle arrest at the G2/M transition. Molecular docking simulations reveal the binding mechanism of the most active antiproliferative agents.